Multi-faceted palliative care intervention: aged care nurses' and care assistants' perceptions and experiences - Phillips, J. L.; Davidson, Patricia; Jackson, D.; Kristjanson, Linda (Blackwell Publishing Ltd, 2008)
AIM: This paper is a report of a study to describe residential aged care nurses' and care assistants' perceptions of a multi-faceted palliative care intervention to identify potential areas to be addressed during subsequent action research phases. BACKGROUND: Action research was used to enhance the delivery of a palliative approach in residential aged care. The chronic care model guided the development of a multi-faceted intervention. This involved the: (1) establishment of a 'link nurse' role; (2) learning and development strategies for nurses, care assistants and general practitioners; (3) use of multi-disciplinary team meetings; and (4) access to specialist consultation. METHOD: A purposive sample (n = 28) of aged care nurses and care assistants participated in a series of four focus groups conducted in July 2005. Thematic content analysis of the transcripts was performed. FINDINGS: Four themes emerged: (1) targeted education can make a difference; (2) a team approach is valued; (3) clinical assessment tools are helpful; and (4) using the right language is essential. Participants described increased understanding of palliative care concepts, enhanced competencies, greater confidence to deliver palliative care and a desire to adopt a multi-disciplinary approach to care planning. CONCLUSION: Sustaining a culture that is committed to ongoing learning and development interventions and creating multi-disciplinary teams in the aged care setting is critical to embedding a palliative approach. The chronic care model is a useful framework to guide the development of interventions leading to better palliative care outcomes for residents and their families.